POSREM (Posyandu Remaja) sebagai Wadah untuk Edukasi Bahaya Merokok pada Remaja - Maslikhah Maslikhah; Hilda Prajayanti (LPPM Akbid Harapan Ibu Pekalongan, 2023)
Adolescence is a transition period from children to adults. Teenagers are usually more interested in something new so that teenagers will try to do new things that are not necessarily with the right knowledge, attitudes and actions. Teenage problems are very complex, one of which is smoking behavior and free sex. Free sex can occur by changing boyfriends and girlfriends and smoking can occur due to the life style of adolescents who are influenced by the surrounding environment. The purpose of this activity is to provide education to adolescents about the importance of preventive efforts of juvenile delinquency in terms of free sex and smoking behavior. The method used is by giving pretest, filling in the material, discussion, examination and ending with filling in the post test. The results of this program obtained an increase in adolescents' knowledge about the importance of preventing juvenile delinquency, especially free sex and smoking behavior, which can be seen in the mean value increased by 18.16%. This shows that providing education about the importance of preventing juvenile delinquency, especially free sex and smoking, can increase knowledge.